2019
DOI: 10.3389/fpsyt.2019.00728
|View full text |Cite
|
Sign up to set email alerts
|

Mothering, Substance Use Disorders and Intergenerational Trauma Transmission: An Attachment-Based Perspective

Abstract: Background: A growing body of research underlines that interpersonal trauma in childhood leads to heightened susceptibility for substance use disorders (SUDs) in later life. Little research has been conducted on parenting experiences of mothers in recovery from substance use, taking into account their own upbringing as a child and the potential aftermath of interpersonal childhood trauma. Methods: Through in-depth qualitative interviews, 23 mothers with SUDs reflected on parenting experiences and parent-child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 134 publications
5
24
0
Order By: Relevance
“…These results are consistent to the previous studies that indicated that the average time from abstinence to relapse varies from 4 to 32 days for tobacco, alcohol, and opiates [2,5,11,33]. They are also supported by the prior studies that showed that substance use following treatment typically is higher up to more than 75 % in the 3-6-month period following treatment [30,34]. Considering South African statistics in 2013, 22 % of admissions into treatment centres were relapsed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent to the previous studies that indicated that the average time from abstinence to relapse varies from 4 to 32 days for tobacco, alcohol, and opiates [2,5,11,33]. They are also supported by the prior studies that showed that substance use following treatment typically is higher up to more than 75 % in the 3-6-month period following treatment [30,34]. Considering South African statistics in 2013, 22 % of admissions into treatment centres were relapsed.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the results of this study suggest that the PUD who experienced low accessibility to drugs had a greater risk to relapse than the patients who appropriately accessed to required health treatments. This result is in line with the previous studies that confirmed that environmental risk factors increase the risk of relapse such as the increased availability and accessibility of drugs [19,21,34,35,37]. The results revealed that patients using multiple substances such as two to three substances were more likely to relapse than those only used one substance.…”
Section: Discussionsupporting
confidence: 91%
“…Parallel to the findings of prior research, this study found that the threat of losing parental authority is the most frequently endorsed barrier to treatment among female substance users with children (Meulewaeter et al, 2019), who attempt to stay under the radar of the social welfare system. However, for some participants it serves as a crucial reason to initiate treatment, either compulsorily or voluntarily.…”
Section: Discussionsupporting
confidence: 74%
“…A lack of healthy relationships or experiences of trauma are features often present in the narratives of women who have experienced addiction (Covington, 2002;Meulewaeter et al, 2019). As Covington (2002) explains, experiences of trauma expand beyond the suffering of direct violence to also include the witnessing of violence and the stigmatisation of these experiences, with women at a greater risk of experiencing harm from a partner or loved one.…”
Section: Understanding the Role Of Relationships In Recovery For Womenmentioning
confidence: 99%